Evaluación de la adición de clavo de olor al 1 y 2 % como promotor de crecimiento en la alimentación de cobayos (Cavia porcellus) en el centro experimental Salache, Cotopaxi - Sánchez Aimacaña, Jessica Gabriela (2016)
This research was conducted in the province of Cotopaxi, Latacunga Canton, Eloy Alfaro parish in the Experimental and Production Center Salache. The same was done in the growth stage with the use of clove. The main objective is to evaluate the addition of clove 1% and 2% as growth promoter in feed for guinea pigs (Cavia porcellus). Here a completely randomized design, with three treatments experienced, Treatment 0 (feed mixture + commercial feed as control treatment) was handled; Treatment 1 (feed mixture + balanced with the addition of 1% clove); Treatment 2 (feed mixture + balanced with the addition of 2% of cloves); The trial consisted of ten experimental units per treatment, total thirty male guinea pigs weaned followed by an adaptation period of one week then started with the trial that lasted eight weeks were used....